2015
DOI: 10.1590/0104-6632.20150324s00003518
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTION OF STABILITY AND THERMAL CONDUCTIVITY OF SnO2NANOFLUID VIA STATISTICAL METHOD AND AN ARTIFICIAL NEURAL NETWORK

Abstract: -Central composite rotatable design (CCRD) and artificial neural networks (ANN) have been applied to optimize the performance of nanofluid systems. In this regard, the performance was evaluated by measuring the stability and thermal conductivity ratio based on the critical independent variables such as temperature, particle volume fraction and the pH of the solution. A total of 20 experiments were accomplished for the construction of second-order polynomial equations for both target outputs. All the influentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As can be observed, the Df and sum of square of lack of t is zero. The lack of t contain the insigni cant parameters [31]. Therefore, it can be concluded that the proposed models in Table 1 and Table 2 involve only the signi cant factors.…”
Section: The Analysis Of Variance Studymentioning
confidence: 94%
See 1 more Smart Citation
“…As can be observed, the Df and sum of square of lack of t is zero. The lack of t contain the insigni cant parameters [31]. Therefore, it can be concluded that the proposed models in Table 1 and Table 2 involve only the signi cant factors.…”
Section: The Analysis Of Variance Studymentioning
confidence: 94%
“…The graphical approach can show the relationship between factors and response. In this method, the residuals are converted to the studentized residuals and are plotted versus main factors, run number or on normal probability [31,32]. The rst assumption of the ANOVA is the normality of error that can be veri ed using normal probability plot.…”
Section: The Analysis Of Variance Studymentioning
confidence: 99%
“…The samples' re ectances were measured using visible spectrophotometry, under D65 illuminant at 10° (Konica-Minolta CM 3600d) (Kazemi-Beydokhti et al, 2015).…”
Section: Dyeing Process Designmentioning
confidence: 99%
“…Soft computing methods provide several tools to show nonlinear input-output mapping and solve a variety of nonlinear and complex problems. Among these methods, the clustering algorithm is applied for classifying elements into categories or clusters on the basis of their similarity and can be also used for anomaly detection in industrial applications (Rodriguez et al, 2014;Elhamifar et al, 2013;Birant et al, 2007;Assidjo et al, 2008;Kazemi-Beydokhti et al, 2015). Besides, the combination of clustering algorithm and CFD method is rarely researched.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%